Defining and measuring motor imagery in children: mini review - Saleem, Ghazala T. (Frontiers in Psychology, 2023)
Motor Imagery (MI) is the ability to engage in the mental representation of a task consciously or automatically without generating a voluntary movement. While the construct of MI and its various dimensions have been comprehensively studied in adults, research remains limited in children. Children as young as five years old can engage in MI, and this engagement is crucial to their motor development and skill acquisition. Further, the degree of skill achievement is directly linked to MI responsiveness. Clinicians and researchers often measure MI responsiveness in children to facilitate skill development and retention. However, few measures exist that can appropriately assess MI responsiveness in children. To date, a focused review examining the MI dimensions in children as well as comparing the characteristics of MI measures in children is lacking, and thus a research gap exists. This paper examines past and current research describing MI ability in children from the theoretical, developmental, and neurological lens and systematically analyzes the properties of three widely used operations –the Movement Imagery Questionnaire in Children (MIQ-C), the Florida Praxis Imaginary Questionnaire (FPIQ-C), and the Mental Chronometry Paradigm (MCP) –to measure MI and its dimensions in children.